Effects of particle size and storage length on the fermentation pattern and ruminal disappearance of rehydrated corn grain silage hammer mill processed - Gervásio, J. R.S. [UNESP] (2023)
The aim of this study is to determine whether the particle size interacts with the storage length to affect the fermentation pattern and the ruminal disappearance of rehydrated corn grain silage (RCGS). It was also assessed whether particle size affects the minimum storage time in relation to the disappearance of ruminal dry matter (DMD). The treatments consisted of six mean particle sizes of RCGS ground in a hammer mill, resulting from different grinding degrees (0.97 mm, 1.11 mm, 1.35 mm, 1.51 mm, 1.69 mm, and 1.75 mm), which were stored for 15, 30, 60, 120, and 240 days. Data were analyzed as repeated measures using the MIXED procedure. When effects of interaction between factors were identified, data were analyzed as polynomial contrasts. Ruminal in situ DM disappearance was modeled across different storage lengths using a non-linear regression model. Prolamin was higher in 1.69 mm and 1.51 mm silages at 15 and 30 days of storage (P < 0.05). Also was observed a decrease in prolamin at 240 days of storage (P < 0.01). The pH of silages was lower after 60 days of storage (P < 0.01), a reduction which is linked to the smaller particle size in 1.11 mm and 1.75 mm silages (P < 0.01). No interaction effects were identified between storage length and DM loss. A greater loss occurred in 1.69 and 1.75 mm silages at 15, 30, and 240 days. At 15 and 60 days, a quadratic behavior was observed, varying according to the increase in particle size. Acetic acid, ethyl lactate, and 1,2 propanediol concentrations increased with storage length (P < 0.01). Lactic acid concentration was affected at 240 days, exhibiting a quadratic behavior according to particle size. The growth pattern of LAB exhibited a quadratic behavior as the mean RCGS particle size increased. The aerobic stability of silages increased after 60 days of storage (P < 0.01), and an interaction effect was found in relation to particle size. According to the Broken-line linear-linear model, maximum disappearance increments were observed at 36, 38, 39, 50, 54, and 46 days of storage for silages with particles measuring 0.97 mm, 1.11 mm, 1.35 mm, 1.51 mm, 1.69 mm, and 1.75 mm, respectively. All silages exhibited an adequate fermentation, and the minimum storage length depended on the particle size of RCGS ground in a hammer mill.